2002
DOI: 10.1046/j.1528-1157.2002.32401.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Epilepsy Surgery with Intraoperative MR Imaging

Abstract: Summary: Purpose:The surgical treatment of medically intractable temporal lobe epilepsy includes the resection of temporal lobe structures. Although the reported seizure-free outcomes are highly variable, there is growing evidence that the extent of resection of the mesiotemporal lobe directly correlates with seizure control.Methods: A moveable, high-field intraoperative magnetic resonance (MR) system was used to monitor and optimize the resection of the amygdala and hippocampus in 14 epilepsy patients. Fourte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…23,41 To our knowledge, only a few studies on epilepsy surgery performed with the aid of 1.5-T iMRI systems exist. 5,21,22,26,46 Neuronavigation became popular recently for lesionectomy of temporal and extratemporal regions, 6 lesions of the insular region, 49 and callosotomy. 20 With more than 15 years of experience with neuronavigation and intraoperative imaging, our department successfully developed and integrated multimodal imaging techniques in daily neurosurgery.…”
Section: Functional Mri Tractography (Dti) Neuronavigation and Imrimentioning
confidence: 99%
“…23,41 To our knowledge, only a few studies on epilepsy surgery performed with the aid of 1.5-T iMRI systems exist. 5,21,22,26,46 Neuronavigation became popular recently for lesionectomy of temporal and extratemporal regions, 6 lesions of the insular region, 49 and callosotomy. 20 With more than 15 years of experience with neuronavigation and intraoperative imaging, our department successfully developed and integrated multimodal imaging techniques in daily neurosurgery.…”
Section: Functional Mri Tractography (Dti) Neuronavigation and Imrimentioning
confidence: 99%
“…There have been many groups who have implemented iMR into their image-guided surgical systems, and a sampling of the research can be found in the literature. [2][3][4][5][6][7] While iMR does provide a complete set of updated volumetric data, there are some disadvantages. Currently, it is difficult, time-consuming, and expensive to install an intraoperative magnetic resonance unit into an operating suite.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the intraoperative MRI technique has been mostly applied in neurosurgical resection of tumors, rather than in epilepsy surgery. For the two available iMRI applications in epilepsy surgery, the epileptic foci were both located in the temporal lobe (3,12). In this paper, we applied the iMRI technique, combined with microscopic-based neuronavigation to 31 patients in Group II.…”
Section: Times Of Imri Scansmentioning
confidence: 99%